Acute Liver Failure in a Patient Treated With Metamizole - Krisai, Philipp; Rudin, Deborah; Grünig, David; Scherer, Kathrin; Pichler, Werner; Terracciano, Luigi; Krähenbühl, Stephan (Frontiers in Pharmacology, 2019)
We report on a patient who developed acute liver failure while being treated with metamizole. After liver transplantation, the patient recovered rapidly. Liver biopsy showed massive necrosis and lobular infiltration of lymphocytes. A lymphocyte transformation test performed twenty months after transplantation was positive for metamizole. In vitro investigations with N-methyl-4-aminoantipyrine (MAA) and 4-aminantipyrine (AA), the two active metabolites of metamizole, did not reveal relevant toxicity in HepG2 and HepaRG cells. The demonstration of activated lymphocytes by the lymphocyte transformation test and the absence of relevant cytotoxicity by MAA and AA in hepatocyte cell lines suggest an immunological mechanism of metamizole-associated hepatotoxicity.